Nucleon Structure Functions from Operator Product Expansion on the Lattice - Chambers, A. J.; Horsley, R.; Nakamura, Y.; Perlt, H.; Rakow, P. E. L.; Schierholz, G.; Schiller, A.; Somfleth, K.; Young, R. D.; Zanotti, J. M. (Physical review letters, 2017)
Deep-inelastic scattering, in the laboratory and on the lattice, is most instructive for understanding how the nucleon is built from quarks and gluons. The long-term goal is to compute the associated structure functions from first principles. So far this has been limited to model calculations. In this Letter we propose a new method to compute the structure functions directly from the virtual, all-encompassing Compton amplitude, utilizing the operator product expansion. This overcomes issues of renormalization and operator mixing, which so far have hindered lattice calculations of power corrections and higher moments.